Assessing biomarkers in a real-world severe asthma study (ARIETTA). (June 2016) - Buhl, Roland; Korn, Stephanie; Menzies-Gow, Andrew; Aubier, Michel; Chapman, Kenneth R.; Canonica, Giorgio W.; Picado, César; Martin, Nicolas; Escobar, Ramon Aguiar; Korom, Stephan; Hanania, Nicola A.
Abstract: The prognostic value of asthma biomarkers in routine clinical practice is not fully understood. ARIETTA (NCT02537691) is an ongoing, prospective, longitudinal, international, multicentre real-world study designed to assess the relationship between asthma biomarkers and disease-related health outcomes. The trial aims to enrol and follow for 52 weeks approximately 1200 severe asthma patients from approximately 160 sites in more than 20 countries. Severe asthmatics, treated with daily inhaled corticosteroid (≥500 μg of fluticasone propionate or equivalent) and at least 1 second controller medication are to be included. In this real-world study, patients will be treated according to the investigator's routine clinical practices and no treatment regimen will be implemented as part of the trial. At baseline and again at 26 and 52 weeks, FEV1, FeNO, serum periostin, blood eosinophil count and serum IgE will be measured. Asthma-related symptom and quality of life questionnaires will be administered at the visits and during telephone interviews at Weeks 13 and 39. Data about medication use, asthma exacerbation data, asthma-related healthcare utilization and events raising safety concerns will also be collected. This study design, unique in both its scope and scale, will address fundamental unanswered questions regarding asthma biomarkers and their interrelationship, as well as predict deviations in the course of asthma in a real-world setting. Highlights: Utility of biomarkers to predict asthma exacerbations and lung function decline. Considering biomarkers in a real-world setting in those with severe asthma. Evaluating the relationship of biomarkers to each other. Understanding the prognostic value of biomarkers for future asthma events/control.